A reactive oxygen species–related signature to predict prognosis and aid immunotherapy in clear cell renal cell carcinoma - Liu, Hongxiang; Luo, Yong; Zhao, Shankun; Tan, Jing; Chen, Minjian; Liu, Xihai; Ye, Jianheng; Cai, Shanghua; Deng, Yulin; Li, Jinchuang; He, Huichan; Zhang, Xin; et al. (Frontiers in Oncology, 2023)
Clear cell renal cell carcinoma (ccRCC) is a malignant disease containing tumor-infiltrating lymphocytes. Reactive oxygen species (ROS) are present in the tumor microenvironment and are strongly associated with cancer development. Nevertheless, the role of ROS-related genes in ccRCC remains unclear. We describe the expression patterns of ROS-related genes in ccRCC from The Cancer Genome Atlas (TCGA) and their alterations in genetics and transcription. An ROS-related gene signature was constructed and verified in three datasets. Our signature was constructed based on GCLM, IPCEF1, MsrA, and SBNO2 genes. More importantly, protein expression levels of GCLM, MsrA, and SBNO2 were detected by immunohistology in our own ccRCC samples. The high-risk group of ccRCC patients suffered lower overall survival rates. As an independent predictor of prognosis, our signature exhibited a strong association with clinicopathological features. An accurate nomogram for improving the clinical applicability of our signature was constructed. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed that the signature was closely related to immune response, immune activation, and immune pathways. The comprehensive results revealed the high-risk group was associated with high infiltration of regulatory T cells and CD8+ T cells and more benefited from targeted therapy. In addition, immunotherapy had better therapeutic effects in the high-risk group. Our signature paved the way for assessing prognosis and developing more effective strategies of immunotherapy and targeted therapy in ccRCC.